"Atypical" salivary gland fine needle aspiration: Risk of malignancy and interinstitutional variability. Issue 12 (29th September 2017) - Wang, He; Malik, Aatika; Maleki, Zahra; Rossi, Esther Diana; Ping, Bo; Chandra, Ashish; Ali, Syed Z.; Fadda, Guido; Wang, Jindong; Arab, Seyedeh Elham; Zhao, Huaqing; Jhala, Nirag
Abstract : Background: Fine needle aspiration (FNA) is widely used in the diagnosis of salivary gland lesions. Salivary gland FNAs are often difficult to diagnose because of morphologic heterogeneity, a small but significant number of the FNAs yield "atypical" diagnosis. However, systematic evaluation of the risk of malignancy (ROM) of the atypical diagnoses across institutions and the variability of ROM among institutions are still lacking. Methods: Salivary gland FNAs from five tertiary medical centers of United States, Europe and China were reviewed. Cases with "atypical" diagnosis and histological follow‐up were included in this study. The diagnostic category of "atypical" was adopted from Milan System for Reporting Salivary Gland Cytopathology (MSRSGC, personal communication). Results: Among the 12, 606 salivary gland FNAs, 504 (4.0%) cases were reported as "atypical", with 154 cases (30.6%) having histological follow‐ups. Histological follow‐ups revealed 94 malignant tumors (61.0%, 57 lymphomas, 33 carcinomas, 2 sarcomas, 1 metastatic melanoma, 1 metastatic neuroblastoma), 33 benign tumors (21.4%), and 25 benign lesions (16.2%). ROM in the subset of "atypical" cases with histological follow‐up from different institutions vary from 73.08% to 0.00%, the Pearson chi 2 = 24.38 and P < .001. Conclusions: More than half of the subset of "atypical" salivary gland FNAs with histological resection turned out to be malignant tumors; another one‐fourth were benign neoplasms. Further, the highly variable ROMs of the "atypical" category amongst different institutions likely reflect the variable practices at each individual institution.